Advanced engineering and technology : proceeding of the 2014 Annual Congress on Advanced Engineering and Technology (CAET 2014), Hong Kong, 19-20 April 2014 /: proceeding of the 2014 Annual Congress on Advanced Engineering and Technology (CAET 2014), Hong Kong, 19-20 April 2014. ([2014]) - Unknown
No abstract available